2000
DOI: 10.1001/archpedi.154.8.827
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Protein Concentration in Pediatric Patients

Abstract: Objectives: To define clinically relevant reference ("normal") values for cerebrospinal fluid (CSF) protein concentrations in pediatric patients who were evaluated for meningitis by traditional criteria and by enteroviruspolymerase chain reaction (EV-PCR). Design and Patients:A cohort of 906 consecutive pediatric patients to receive CSF analysis at St Louis Children's Hospital, St Louis, Mo, from June 1, 1998, to December 31,1998, was studied for clinical and laboratory data. Age-dependent CSF protein concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 12 publications
2
41
1
Order By: Relevance
“…Pleocytosis was defined as a CSF cell count of Ͼ22 cells/mm 3 if the patient's age was Ͻ4 weeks, Ͼ15 cells/mm 3 if the patient's age was 4 to 8 weeks, and Ͼ5 cells/mm 3 if the patient's age was Ͼ8 weeks (1). The cutoffs to identify elevated levels of CSF protein were those determined by a study at our institution in which EV RT-PCR was performed on all specimens to eliminate any samples from patients with unsuspected EV infections (19). Those cutoffs were as follows: Ն111 mg/dl for patients aged Յ2 months, Ն79 mg/dl for patients aged Ͼ2 months to 4 months, Ն34 mg/dl for patients aged Ͼ4 months to 14 years, Ն37 mg/dl for patients aged Ͼ14 years to 18 years, and Ն46 mg/dl for patients aged Ͼ18 years.…”
Section: Methodsmentioning
confidence: 99%
“…Pleocytosis was defined as a CSF cell count of Ͼ22 cells/mm 3 if the patient's age was Ͻ4 weeks, Ͼ15 cells/mm 3 if the patient's age was 4 to 8 weeks, and Ͼ5 cells/mm 3 if the patient's age was Ͼ8 weeks (1). The cutoffs to identify elevated levels of CSF protein were those determined by a study at our institution in which EV RT-PCR was performed on all specimens to eliminate any samples from patients with unsuspected EV infections (19). Those cutoffs were as follows: Ն111 mg/dl for patients aged Յ2 months, Ն79 mg/dl for patients aged Ͼ2 months to 4 months, Ն34 mg/dl for patients aged Ͼ4 months to 14 years, Ն37 mg/dl for patients aged Ͼ14 years to 18 years, and Ն46 mg/dl for patients aged Ͼ18 years.…”
Section: Methodsmentioning
confidence: 99%
“…CSF samples were included in this study providing they revealed a typical profile of aseptic meningitis with elevated levels of protein (Ͼ0.45 g/liter) and/or nuclear cells (Ͼ6 cells/mm 3 ), normal glucose levels, negative Gram stain results, and negative bacterial and fungi cultures (15). Virus isolation had been prospectively performed for each CSF sample on human diploid fibroblasts (MRC-5) and rhesus monkey kidney cells (MA-104) as previously described (7).…”
mentioning
confidence: 99%
“…Elevated protein content in CSF may be indicative of a pathologic process and levels above 1.0 g/l in neonates and 0.35 g/l in preadolescent children can be reached (Wong et al 2000).…”
Section: Test Liquids For Characterisation Of Protein Adsorptionmentioning
confidence: 99%